2008
DOI: 10.1124/jpet.108.141176
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Neurokinin-2 Receptor in Airway Smooth Muscle Stretch-Activated Contractions Assessed in Perfused Intact Bovine Bronchial Segments

Abstract: The airway response to deep inspirations (DIs) in asthmatics has been shown to be ineffective in producing bronchodilation and can even cause bronchoconstriction. However, the manner by which a DI is able to cause bronchoconstriction remains ambiguous. We sought to investigate the pathway involved in this stretch-activated contraction and whether this contraction is intrinsic to airway smooth muscle (ASM). In brief, intact bovine bronchial segments were dissected, and side branches were ligated and then mounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 40 publications
2
23
2
Order By: Relevance
“…2A). A more detailed description of this protocol is outlined in our previous study (Hernandez et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2A). A more detailed description of this protocol is outlined in our previous study (Hernandez et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Using intact bovine bronchial segments, we have shown that airway R stretch depends on contractile machinery priming and the magnitude of airway stretch. Moreover, in intact bovine bronchi, these responses possess nonmyogenic characteristics caused by the requirement of sensory neuronal input mediated by NK-A acting through the NK 2 receptor (Hernandez et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations